Full Mouth Reconstruction of a Skeletal Class II Division 1 Patient with Adenoid Cystic Carcinoma Using an Interim Immediate Obturator and a Definitive Obturator - Mehran Bahrami; Seyed Mehran Falahchai (Case Reports in Dentistry)
A 61-year-old female patient with adenoid cystic carcinoma (ACC) of the right maxilla and Angle class II division 1 malocclusion had received a subtotal maxillectomy in right side and used a conventional clasp-retained obturator. After implants placement, a maxillary interim immediate obturator (IIO) and then a definitive obturator using six endosseous implants were fabricated. During one-year follow-up, the patient was completely satisfied. Ideally, after implants placement in edentulous patients suffering from hemimaxillectomy, an implant-supported obturator (ISO) is designed in order to prevent nasal reflux and to improve speech and swallowing. However, in the following case, because of skeletal class II division 1 malocclusion and implants insertion in the premaxilla, using an ISO was impossible because it would cause excessive upper lip protrusion and lack of anterior teeth contact. Therefore, a five-unit implant-supported fixed partial denture (FPD) was fabricated in the maxillary anterior segment so that anterior teeth contacts were possible and the patient’s normal lip support was achieved. A bar and three ball attachments were used in the maxillary posterior segment. A closed-hollow-bulb ISO was preferred. Conventional ISO in these patients results in several problems. Using a maxillary anterior FPD along with ISO caused satisfactory results in the current patient.